2014
DOI: 10.1130/g34886.1
|View full text |Cite
|
Sign up to set email alerts
|

Heading down early on? Start of subduction on Earth

Abstract: International audienceHow the Earth’s earliest crust was formed and when present-day plate tectonics (i.e., subduction) and life commenced remain fundamental questions in Earth sciences. Whereas the bulk composition of the crust is similar to that of rocks generated in subduction settings, it does not necessarily follow that melting and crust formation require subduction. Many workers suggest that subduction may have only commenced toward the end of the Archean or later. Here we observe that both the stratigra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
79
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(85 citation statements)
references
References 31 publications
6
79
0
Order By: Relevance
“…In any case, if life is present in the subduction zone forearc, it has far-reaching implications as recent studies suggest that environments resembling those both within and below the Mariana serpentinite mud volcanoes were already present on the early Earth (58,59). Thus, even if modern-type subduction was not fully established in the Hadean and Archean, Mariana forearclike deep subsurface environments may have allowed early forms of life to thrive, despite violent phases such as the so-called Late Heavy Bombardment, a period of intensive meteorite bombardment around 3.9 Ga (60).…”
Section: Discussionmentioning
confidence: 99%
“…In any case, if life is present in the subduction zone forearc, it has far-reaching implications as recent studies suggest that environments resembling those both within and below the Mariana serpentinite mud volcanoes were already present on the early Earth (58,59). Thus, even if modern-type subduction was not fully established in the Hadean and Archean, Mariana forearclike deep subsurface environments may have allowed early forms of life to thrive, despite violent phases such as the so-called Late Heavy Bombardment, a period of intensive meteorite bombardment around 3.9 Ga (60).…”
Section: Discussionmentioning
confidence: 99%
“…Conduction is much less efficient at transferring thermal energy than is convection-advection (Sleep 2000). Therefore, primitive plate-tectonic processes evidently began during Hadean time (i.e., ϳ4.4-4.0 Ga; Hopkins et al 2008;Foley et al 2014;Turner et al 2014). Thickening of lithospheric platelets probably occurred gradually, reflecting thermal relaxation of the planet.…”
Section: Formation Of the Earthmentioning
confidence: 99%
“…But how and when did plate-tectonic processes commence, very early in Earth history (Kröner 1981;Ernst 1983;Sleep 1992Sleep , 2005Komiya et al 1999;Parman et al 2001;Polat et al 2002;Smithies et al 2003Smithies et al , 2005aCondie 2005;Cawood et al 2006;Dilek and Polat 2008;Nutman and Friend 2009;Sleep et al 2014;Turner et al 2014) or much later (Davies 1992;Hamilton 1998Hamilton , 2003Hamilton , 2007Stern 2005Stern , 2007Stern , 2008Dewey 2007;Brown 2008;Shirey and Richardson 2011;Shirey et al 2013)? In a sense, this is just a terminological problem, for the early, hot mantle must have circulated beneath a mobile outer rind since solidification of the postulated magma ocean.…”
Section: Introductionmentioning
confidence: 99%
“…Harrison [68] and Hopkins et al [69] interpreted the record of Hadean zircons preserved within younger sediments to indicate that subduction was taking place at the time. Turner et al [90] note that volcanic rocks near Nuvvuagittuq, Québec, which are at least as old as 3.8 Ga, and possibly older than 4.4 Ga, resemble those from the Izu-Bonin-Mariana forearc (the region between the typical location of volcanoes and the trench). Pons et al [91] showed the similarity between 3.7 and 3.8 Ga serpentines from Isua, Greenland, and modern forearc serpentines.…”
Section: (B) Ancient Subductionmentioning
confidence: 99%
“…Returning to mechanics, Turner et al [90] also invoked modern subduction to explain their early Archaean rock samples. The thermal aspects of this process are essential to the fate of CO 2 within the oceanic crust.…”
Section: (B) Ancient Subductionmentioning
confidence: 99%